1978
DOI: 10.1111/j.1532-5415.1978.tb01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's Disease: Improvement with an Anticoagulant‐Psychotherapy Regimen

Abstract: A 45-year old women with Huntington's disease (HD) was followed for three years while under an anticoagulant-psychotherapy regimen. The chorea disappeared and the patient improved rather than deteriorating as predicted. All psychotropic drugs were discontinued. This case of reversal of the disease may help to confirm the hypothesis that HD is probably due to circulatory insufficiency in the substantia nigra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The management of these problems, from a behavioral viewpoint, is not specific to Huntington's disease and involves the same environmental restrictions and general supportive care administered to other psychotic or demented patients. It has been suggested that psychotherapy aimed specifically at allaying anxiety and reducing stress may improve cerebral blood flow and thereby abate chorea (25). Huntington's disease, however, appears to be a primary neurodegenerative disorder and there is little evidence to support a hypothesis for vascular insufficiency in the striatum (26).…”
Section: Psychiatric Therapymentioning
confidence: 99%
“…The management of these problems, from a behavioral viewpoint, is not specific to Huntington's disease and involves the same environmental restrictions and general supportive care administered to other psychotic or demented patients. It has been suggested that psychotherapy aimed specifically at allaying anxiety and reducing stress may improve cerebral blood flow and thereby abate chorea (25). Huntington's disease, however, appears to be a primary neurodegenerative disorder and there is little evidence to support a hypothesis for vascular insufficiency in the striatum (26).…”
Section: Psychiatric Therapymentioning
confidence: 99%